Harmful alcohol use and frequent use of marijuana among lifetime problem gamblers and the prevalence of cross-addictive behaviour among Greenland Inuit: evidence from the cross-sectional Inuit health in transition Greenland survey 2006–2010 - Christina Viskum Lytken Larsen; Tine Curtis; Peter Bjerregaard (International Journal of Circumpolar Health, 2013)
Background and objectives. Public health research has pointed to alcohol and substance abuse as the most significant public health challenges in Greenland with the negative impact on families and communities that entail, but few studies have investigated the role of problem gambling as addictive behaviour among Inuit. The objectives of the present study were to investigate (a) the association between lifetime problem gambling and harmful alcohol use as well as frequent use of marijuana and (b) the prevalence of cross-addictive behaviour among Greenland Inuit. Design. A representative cross-sectional study among Greenland Inuit (n=2,189). Data was collected among adults (18+) in 8 towns and 13 villages in Greenland from 2006–2010. Lifetime problem gambling, harmful alcohol use and frequent use of marijuana were measured through a self-administered questionnaire. Results. The odds ratio for harmful alcohol use and frequent use of marijuana was significantly higher among lifetime problem gamblers compared to non-problem gamblers/non-gamblers. One or more addictive behaviours were present among more than half of the men (53%) and one third of the women (37%), and the co-occurrence of lifetime problem gambling with either harmful alcohol use, frequent use of marijuana or both was found among 12.2% of men and 3.7% of women. The prevalence of one or more addictive behaviours was 44% in households with children. Conclusions. For lifetime problem gamblers, the gambling problems were more often than not combined with harmful alcohol use, frequent use of marijuana or both – especially among men. The high prevalence of addictive behaviours in households with children indicates that many families are presently affected negatively by alcohol, gambling and marijuana. This suggests that pathological gambling should be included systematically in future public health strategies, treatment programs and interventions in Greenland.